Budidaya Telur Maggot Lalat Black Soldier Flies (BSF) Skala Rumah Tangga Sebagai Pakan Ikan (International Forum of Researchers and Lecturers, 2023)
The purpose of this writing is to find out the procedure for cultivating Black Soldier Flies (BSF) maggot eggs on a household scale as fish feed. The stages of activities carried out are: 1) Consultation to mentors, 2) In-depth research, 3) Collection of materials. Maggot is a kind of natural food rich in protein. Maggot contains 41-42% crude protein, 31-35% ether extract, 14-15% ash, 4.8-5.1% calcium, and 0.6-0.63% phosphorus in dry form. To maintain BSF larvae, a suitable and quality substrate is needed. Optimal temperature and humidity affect the productivity of females in producing quality eggs. The mating process of BSF flies is strongly influenced by environmental factors and the behavior of adult insects